Citations in literature review chapters of TESOL master’s theses by Vietnamese postgraduates - Nguyen Thi Thuy Loan,; Issra Pramoolsook, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Citing other works poses difficulties for novice writers, especially the non-native English speaking students in their first experience of writing for academic purposes; the master’s (M.A.) thesis. However, few studies were conducted on these students’ citations in their M.A. theses. This paper, therefore, presents the study of in-text citations in 24 literature review (LR) chapters of TESOL M.A. theses written by Vietnamese students. Employing the Antconc software, Thompson and Tribble’s (2001) framework for citation types and functions, and discourse-based interviews with the actual thesis writers and their thesis supervisors, the study confirmed the claim that non-native novice writers cannot fully learn crucial citation practices from mere reading of the guidelines. Besides these writers’ preference for integral citations and a very limited number of citation functions used in their LR chapters, this study also identified the presence of several secondary citations, the students’ “invented” ways of citing previous researchers, grammatical mistakes and the absence of further discussions of the cited works. These findings tend to render the students’ LR chapters as ineffective, in terms of grammar and the rhetorical functions of LR chapters in synthesizing, arguing and indicating the relevancy of the reviewed literature for the niche of their research to be established. Furthermore, these findings indicate a need for an increased amount of formal instruction in academic writing courses which aims at equipping novice writers with the means to successfully acknowledge the sources and at raising their awareness about the various functions and rhetorical effects of the students’ citations in their academic writing.